Diseño de un sistema de automatización para una cámara de vacío empleada para la calibración de barómetros en presión absoluta. (2022)
In this document, the design of an automated system for a vacuum chamber used for the calibration of absolute pressure measurement instruments will be carried out. The development of the project begins with the identification of the need to automate the calibration process of instruments that work in conditions of absolute pressure; later the characterization of the system is made as it is currently; then, the description of the technical standard that is applied for calibration will be made. In the description of this, it will be clarified which of the sequences will be used for the calibration of the instruments. Later, through selection strategies it was possible to establish that a proportional valve is the appropriate option for automation. With the proportional valve as the best option for the development of automation, a dynamic analysis of the current system is carried out first, for which it will be necessary to carry out an experimental sampling, using Matlab; With this characterization, the selection of a proportional valve and a PLC is made to later make the design of its programming. This is the objective of being able to migrate from a manual calibration to an automated one without producing harmful effects in accordance with the provisions of the DKD-R-6 standard. Subsequently, the maintenance, operation and installation manuals are made in order to be able to deliver a complete and durable design of the automated system. Finally, a cost analysis is made to define the approximate investment that must be made for the automation of the system.